Temperature effects on the behaviour of liquid-laminated embedded glass connections. (1st January 2023) - Volakos, Efstratios; Davis, Chris; Teich, Martien; Lenk, Peter; Overend, Mauro
Highlights: The impact of temperature on the mechanical response of a liquid-laminated embedded glass connection is assessed via experimental, numerical and analytical methods. The stiffness and load-bearing capacity of the connection decreases with increasing temperature. The connection failure mechanism is characterised by glass fracture for temperatures at or below ambient indoor temperature while at higher temperatures it is governed by insert delamination. A simplified analytical model is introduced that adequately captures the load–displacement response of the connection accounting for the time and temperature dependent behaviour of the interlayer. Abstract: Embedded load-bearing laminated glass connections have gained popularity in recent years due to their mechanical performance and aesthetic appeal. However, there is a paucity of data on their structural behaviour across a range of temperatures that may arise in building applications and there is also no simplified mechanics-based model for predicting their load–displacement response. This study addresses these gaps directly through experimental pull-out tests on steel inserts encapsulated in resin-laminated glass performed at various temperatures. The experimental results confirm that the response of the resin interlayer is time / temperature-dependent which therefore significantly affects the connection behaviour. In particular, both the stiffness and strength of the connection decrease with increasing temperature. Similarly, temperature also governs the failure mechanism of the connection. Specifically, temperatures at or below ambient indoor temperature (-10 °C and + 22 ± 2 °C) result in glass fracture whereas at + 50 °C the connection fails due to insert delamination. The numerical (FE) simulations of these tests show that a complex stress/strain state is set up in the vicinity of the embedded insert which correlates well with the experimentally observed failure mechanisms at different working temperatures. Finally, the insights gained along with the data generated from the experimental and numerical work were used to develop a simple analytical tool that predicts the pull-out load–displacement response of the embedded connection at different temperatures and load durations.